Late mismatch negativity of lexical tone at age 8 predicts Chinese children’s reading ability at age 10 - Wu, Han; Zhang, Yixiao (Frontiers in Psychology, 2022)
Background: Deficits in phonological processing are commonly reported in dyslexia but longitudinal evidence that poor speech perception compromises reading is scant. This two-year longitudinal ERP study investigates changes in pre-attentive auditory processing that underlies categorical perception of mandarin lexical tones during the years children learn to read fluently. The main purpose of the present study was to explore the development of lexical tone categorical perception to see if it can predict children’s reading ability. Methods: Both behavioral and electrophysiological measures were taken in this study. Auditory event-related potentials were collected with a passive listening oddball paradigm. Using a stimulus continuum spanning from one lexical tone category exemplar to another, we identified a between-category and a within-category tone deviant that were acoustically equidistant from a standard stimulus. 8-year-old Mandarin speakers participated in both an initial ERP oddball paradigm and returned for a two-year follow up. Results: The between-category MMN and within-category MMN significantly correlate with each other at age 8 but not at age 10. The between-category MMN at age 8 can predict children’s ability at age 10 but the within-category cannot. Conclusion: The categorical perception of lexical tone is still developing from age 8 to age 10. The behavioral and electrophysiological results demonstrate that categorical perception of lexical tone at age 8 predicts children’s reading ability at age 10.